The Functions of the Fishermen’s Sea Pilgrimage to St Peter and St Paul’s Church Fair in the Town of Puck - Tadeusz Palmowski; Lucyna Przybylska (Religions, 2022)
The purpose of this article is to define the function of the Fishermen’s Sea Pilgrimage organised in northern Poland. It is the only boat pilgrimage on the Baltic Sea. One of the authors took part in nearly all the pilgrimages in the years 2004–2022. The authors describe the origins and form of sea pilgrimage against contemporary general trends in pilgrimage in Poland. Next, they present the route, participants, and course of this particular event. The participants of the Fishermen’s Sea Pilgrimage chose Saints Peter and Paul the Apostles’ church in Puck as their destination. The pilgrimage is an illustration of an emerging trend in contemporary pilgrimaging in Poland, characterised by: (1) choosing alternative modes of making the journey, apart from walking; (2) pilgrimage groups not based exclusively on the parishioners’ place of residence; (3) the performance of both religious and non-religious functions.